How do Macroeconomic Shocks affect Expectations? Lessons from Survey Data - Martin Geiger; Johann Scharler (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
We study the revision of macroeconomic expectations due to aggregate demand, aggregate supply and monetary policy shocks. Using zero and sign restrictions, the macroeconomic shocks are identified in a vector autoregressive model in which we include survey data that measure macroeconomic expectations. We find that, in general, people tend to revise expectations in a way that is consistent with standard theory. In particular, people appear to differentiate among the three types of shocks and tend to revise expectations according to the characteristics of the shock. Nevertheless, the accuracy of responses varies with respect to which shock we consider. People process demand shocks most accurately meaning that they revise expectations about economic activity, inflation and the interest rate in a way consistent with standard theory. For supply shocks we find that people at least revise expectations about economic activity and inflation in a theory consistent manner. In the event of monetary policy shocks, people tend to be relatively uncertain about how to process these shocks.
Keywords: E00; E32; D84; 330